2019
DOI: 10.1109/access.2019.2918344
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Tri-Polarized MIMO Channel Properties Based on a Compact Multimode Antenna

Abstract: Based on a planar and compact antenna, extensive measurements are conducted to investigate the behavior of the colocated tri-polarized multiple-input multiple-output (MIMO) system working at 3.5 GHz. Several scenarios with different multipath distributions have been considered, including a reverberation chamber (RC) and also some line-of-sight (LOS) and obstructed LOS (OLOS) real-world indoor environments. Many channel parameters of the MIMO system are analyzed based on the measured data, including cross-polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…Thus, the n s sample of the l seq subsequence in the nth snapshot of the received signal can be denoted by (6), where z n is the complex white Gaussian noise of the nth snapshot and α n,lk represents the fading coefficient of the k l th ray in the nth snapshot. The channel is considered as time-varying for different snapshots.…”
Section: Transmit-receive Signal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the n s sample of the l seq subsequence in the nth snapshot of the received signal can be denoted by (6), where z n is the complex white Gaussian noise of the nth snapshot and α n,lk represents the fading coefficient of the k l th ray in the nth snapshot. The channel is considered as time-varying for different snapshots.…”
Section: Transmit-receive Signal Modelmentioning
confidence: 99%
“…Previous works have proved that multipolarized multiple input multiple output (MIMO) outperforms the corresponding unipolarized MIMO in terms of channel capacity in many situations [6]- [8]. Moreover, dual-polarized antenna configurations outperform single polarization in terms of spatial correlation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that using a tripolarized antenna can get an extra factor of three in channel capacity, relative to the conventional limit using dual-polarized radio signals [13]. Since tripolarized antennas can provide one more degree of freedom and save space, tripolarized MIMO can be an efficient technology to improve the data rate and spectral efficiency [14,15]. Especially, the tripolarized antenna is potential to be used in massive MIMO systems, which would deploy a large number of antenna elements and take up a large space.…”
Section: Introductionmentioning
confidence: 99%
“…In the wireless communication environment with abundant multi‐path resources, several channels of uncorrelated channels can be obtained by using multi‐polarization technology 1 . For a multi‐polarized MIMO system, the effects of polarization coupling and transition depend strongly on the polarimetric scattering characteristic of the environments and three independent subchannels can be supported by the tri‐polarized MIMO system 2 …”
Section: Introductionmentioning
confidence: 99%
“…1 For a multi-polarized MIMO system, the effects of polarization coupling and transition depend strongly on the polarimetric scattering characteristic of the environments and three independent subchannels can be supported by the tri-polarized MIMO system. 2 At present, various types of tri-polarized antennas have been proposed. A tri-polarized antenna consisted of two dipoles and a current loop improve the channel capacity.…”
Section: Introductionmentioning
confidence: 99%